Homoeopathy in Treatment of Gastro Intestinal Disorders - A Retrospective Study (Advancements in Homeopathic Research, 2023)
Introduction: Acid peptic disorder (APD) is a  condition which includes peptic ulcer and gastro  esophageal reflux disease (GERD). The highest  prevalence rate of gastric disorders had been found  out between ages 45-50. Dyspepsia is a term used  for reduced digestion or indigestion. GERD is  referred to as condition where there is regurgitation  of stomach contents to the esophagus. Around 58.7%  of peoples are having acid regurgitation or heart burn  yearly once and 19.8% weekly once. Worldwide  functional gastrointestinal disorder are commonest  now a days, Irritable Bowel Syndrome (IBS) is also  one among them having frequent pain abdomen  and altered bowel habits without any structural gut  abnormalities. Homoeopathy is a system which is  based on individualization, and has principles of  “Like cures like” and law of nature. Materials and methods: A retrospective study had  been conducted with those patients who had attended  the gastroenterology OPD of NHRIMH, Kottayam,  Kerala, for a period of 1 year (from January 2022  to December 2022). Data had been collected from  the case records and it had been found that around  899 patients had visited for the symptoms like  nausea, vomiting, abdominal pain, altered bowel  movements (diarrhea and constipation), bleeding  per rectum, dysuria and hesitancy in urination,etc  for the past 1 year. Aim of the study is to find out  the most frequent age group, diseases affected and  to know the frequently indicated remedies in treating  gastroenterology disorders. Results: 899 patients visited in the defined period  with a highest number of patients (212) were from  the age group of 51-60, female patients were more  than male patients, 758 old patients and 141 new  patients. 214 pateints had diagnosed as gastritis which  is the highest frequency noted. The most frequently  indicated remedies were Nuxvomica in 161 patients  and Suphur in 118 patients.  Conclusion:It is concluded from the study that  gastritis is the most common condition among  patients visiting the above OPD in the defined period  and Nux vomica, Sulphur and Lycopodium were the  most common indicated and prescribed remedies.
Keywords: Gastero intestinal disorder; Acid peptic disorder; gastro esophageal reflux disease; Irritable Bowel Syndrome; homoeopathy